Turn-on Coumarin Precursor: From Hydrazine Sensor to Covalent Inhibition and Fluorescence Detection of Rabbit Muscle Aldolase - Sara Amer; Uri Miles; Michael Firer; Flavio Grynszpan (Molecules, 2024)
Hydrazine, a highly toxic compound, demands sensitive and selective detection methods. Building upon our previous studies with pre-coumarin OFF–ON sensors for fluoride anions, we extended our strategy to hydrazine sensing by adapting phenol protecting groups (propionate, levulinate, and γ-bromobutanoate) to our pre-coumarin scaffold. These probes reacted with hydrazine, yielding a fluorescent signal with low micromolar limits of detection. Mechanistic studies revealed that hydrazine deprotection may be outperformed by a retro-Knoevenagel reaction, where hydrazine acts as a nucleophile and a base yielding a fluorescent diimide compound (6,6′-((1E,1′E)-hydrazine-1,2diylidenebis(methaneylylidene))bis(3(diethylamino)phenol, 7). Additionally, our pre-coumarins unexpectedly reacted with primary amines, generating a fluorescent signal corresponding to phenol deprotection followed by cyclization and coumarin formation. The potential of compound 3 as a theranostic Turn-On coumarin precursor was also explored. We propose that its reaction with ALDOA produced a γ-lactam, blocking the catalytic nucleophilic amine in the enzyme’s binding site. The cleavage of the ester group in compound 3 induced the formation of fluorescent coumarin 4. This fluorescent signal was proportional to ALDOA concentration, demonstrating the potential of compound 3 for future theranostic studies in vivo.